2023
DOI: 10.1111/jopy.12898
|View full text |Cite
|
Sign up to set email alerts
|

One year later: Longer‐term maintenance effects of a digital intervention to change personality traits

Mirjam Stieger,
Christoph Flückiger,
Mathias Allemand

Abstract: ObjectiveRecent research suggests that personality traits can be changed by psychological interventions. However, it is unclear whether these intended personality changes can be maintained or merely reflect ephemeral shifts.MethodThe present study reports 1‐year follow‐up effects of a 3‐month digital intervention for personality trait change. Personality traits were measured before the intervention (pretest: N = 1523), directly after the intervention (posttest: n = 554), and 3 months (follow‐up 1: n = 437) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…By providing an overview the existing literature, the present review helps identifying the most important future directions. Second, although there is initial evidence that VPC is lasting and can be detected by close others 16,54,56 , future research should aim at replicating and extending these findings.…”
Section: Directions For Future Research On Volitional Personality Changementioning
confidence: 99%
See 1 more Smart Citation
“…By providing an overview the existing literature, the present review helps identifying the most important future directions. Second, although there is initial evidence that VPC is lasting and can be detected by close others 16,54,56 , future research should aim at replicating and extending these findings.…”
Section: Directions For Future Research On Volitional Personality Changementioning
confidence: 99%
“…Aggregating 15 effect sizes from three studies with long-term follow-up assessments, we found that personality changed by d = 0.40 (95% CI = [0.05, 0.75]) in the desired direction between pre-intervention assessment and follow-up. For example, the effects of the smartphone intervention PEACH were maintained or even increased over a 3-month and a 1-year follow-up interval 16,54 .…”
Section: Sustainability and Generalizability Of Intervention-induced ...mentioning
confidence: 99%
“…For example, a 15-week intervention study found that volitional and active implementation of change behaviors was associated with changes in Big Five traits (Hudson et al, 2019). A recent randomized controlled trial of a three-month digital-coaching intervention also showed that participants who sought to change their personality traits often succeeded (Stieger et al, 2021), with several observed changes remaining for up to a year later (Stieger et al, 2023). Of course, the intervention studies often focus on selective samples.…”
Section: Challenging the Assumption Of Slow And Incremental Changementioning
confidence: 99%